Telemedicine Device Using IoT for Health Monitoring - Hazadi, Ahmad Haziq Fahmi; Hasliza Hassan; Mohd Kamalrulzaman Md Akhir (Progress in Engineering Application and Technology, 2025)
Telemedicine lets you get medical care from home using digital technology. A small sensor, the MAX30102, is key to this system. It continuously checks your blood oxygen (SpO2) and heart rate (BPM), sending this real-time data directly to doctors. This means medical teams can keep a close eye on your health without you needing to visit a clinic, making healthcare much more accessible. For example, data from May 23rd to 29th showed BPM values ranging from 60 to 125 and SpO2 values from 92% to 99%, proving the system can effectively monitor both normal and abnormal conditions and allow you to receive treatment right from your own home.